THE URGENCY OF PUNISHMENT AGAINST CHILDREN OF NARCOTICS ABUSERS - Handoko, R. Reo; Pratiwi, Siswantari; Johardi, Ali (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
This research aims to analyze the public prosecutor's considerations in proving the elements of the article so that children are categorized as narcotics providers and the public prosecutor's considerations in proving the elements of the article regarding children as perpetrators of narcotics providers. This research is empirical research carried out at the Sidenreng Rappang District Prosecutor's Office. The data obtained is then processed and analyzed using a qualitative descriptive method, namely a method where data is collected, compiled, interpreted and analyzed so as to provide complete information according to the problems faced. The results of this research are: 1) The child's public prosecutor's considerations in making a child's demand letter pay attention to the best interests and future for the child, then in its implementation it refers to juridical reasons related to applicable legal rules and non-juridical ones related to the child's personal, social, family and environment. children and the impact of children's actions on society and the state, as well as children's attitudes in undergoing the trial process; 2) There is conformity in the demands and decisions regarding the proven element, namely the element of providing, even though the element of control is not included in the judge's consideration as an element that is fulfilled in the proof of the indictment in the child's public prosecutor's claim, so even so, the public prosecutor's claim is proven in the element of providing in Article 112 paragraph (1) and paragraph (2) of Law Number 35 of 2009 concerning Narcotics, this strengthens the position of the claim that the claim is appropriate).